Laparoscopic Pyloromyotomy: A Modified Simple Technique - Mohammed Omer Anwar; Yasser Al Omran; Saeed Al-Hindi (EL-Med-Pub, 2015)
Background: A modified laparoscopic pyloromyotomy (LP) technique may provide an alternative to treating infantile hypertrophic pyloric stenosis (IHPS) by improving operative timing with reduction of postoperative complication rates, compared with a three-port trocar system. Methods: Thirty-three infants were treated with IHPS at a single-centre between January 2002 and December 2011. The local surgical incision to the pylorus was performed according to Ramstedt's pyloromyotomy; but with a two-port trocar system (umbilical and right lower abdominal crease ports), following a controlled stab wound into the epigastric region and a 3mm incision to allow introduction of ophthalmic knife. With the aid of atraumatic forceps and camera guidance, the ophthalmic knife was used to carefully incise the seromuscular layer, which allows improved manual tactile sensation compared to ergonomic laparoscopic spreaders. A Benson pyloric spreader was then used to further separate the pyloric muscle layer to complete the procedure. Results: In all 33 infants treated, LP was safely performed with no evidence of duodenal or mucosal perforation with complete pyloromyotomy achieved in each case. The postoperative course was rather uneventful apart from an umbilical wound infection. Conclusion: This modified approach is simple, safe and allows improved operative timing, whilst increasing surgeon's confidence by tactile sensation.